Rupture of the Left Renal Fornix after Vaginal Repair of Postpartum Vesicovaginal Fistula - Rendtorff, R.; Knispel, H. H.; Tunn, R. (Geburtshilfe und Frauenheilkunde, 2014)
Surgical repair of vesicovaginal fistulas carries a risk of postoperative obstruction of the upper urinary tract. In the case described here, a postoperative intramural edema led to urinary retention and subsequent rupture of the renal pelvis. This is a rare but typical urological emergency. If patients complain postoperatively of flank pain, ultrasound should be carried out promptly. If the findings are unclear (no urinary retention despite clinical symptoms), additional computed tomography should be performed to determine whether rupture of the fornix has occurred.
Keywords: urinary incontinence; sonography; vagina